Review on Islamic principle of recreation and outdoor activities for Muslim - Azmee, Nurshamiela; Mohd Yunos, Mohd Yazid; Othuman Mydin, Md Azree (American-Eurasian Network for Scientific Information, 2016)
To create a garden or park on the concept of Islam is not only focused on the characteristics or elements of design, but it also involves the environment, activities and socialization. In order to create a recreational space, there are a few Islamic principles of recreation that we need to follow. Less we can see the recreational park that emphasize the principles, this is because lacking of understanding of the Islamic principles of recreation. Practitioners must provide recreation opportunities and recreational places within the public that have the capacity to meet community needs, including the need to reinforce Muslim cultural practice. The aim of this study is to understand the Islamic principles of recreation. Content analysis is adopted to identify the Islamic principles of recreation. The outcome of this study will enhance the understanding of Islamic principle of recreation, in order to enhance harmonious society thus creating a society of Islamic scholars and creating an environmental Islamic garden design.